Implementation of Multi-Criteria Decision Making (MCDM) for new student majors recommendations - Ikrimach; Murti Retnowo (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2022)
Selection of the right major and according to ability is one way for students to be able to complete their studies at college. Error choosing majors is a problem that is often experienced by students. Many students are confused and careless in choosing a major, there are also those who choose a major based on the wishes of their parents or following a friend, so that during the lecture process there are many obstacles to achieving a bachelor's degree, even having to take education until the end of the study period, Multi Criteria Decision Making is one way that can be used to help recommend prospective students based on their abilities. The program is made specifically for Android-based Smartphones, so that prospective students can try to choose based on values ​​that match the criteria determined by the desired major without having to feel afraid or embarrassed to know whether to be accepted into the department or not. So with the creation of this system, it is expected to be able to provide recommendations to prospective students in choosing majors that are in accordance with their academic abilities and effective study time.